HUBUNGAN PELAKSANAAN TATA TERTIB SEKOLAH DENGAN HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - Novita, Fitri; Sofia, Ari; Hariyanto; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is motivated by the fact that there are still fifth-grade students who have not achieved mastery of learning outcomes. One factor suspected to be related to students' learning outcomes is the implementation of school rules. Therefore, this study aims to determine the relationship between the implementation of school rules and the learning outcomes of fifth-grade students at SD IT Al Muhsin. This study uses a quantitative method with an ex post facto research design. The population, which also served as the sample, consisted of all 78 fifth-grade students. Data were collected through questionnaires and documentation studies. The prerequisites for data analysis included normality and linearity tests, while hypothesis testing used the Pearson Product-Moment correlation formula. The results showed that there is a significant relationship between the implementation of school rules and the learning outcomes of fifth-grade students. These findings indicate that the implementation of school rules serves as a supporting factor in creating an orderly and conducive learning environment, thereby helping to improve students' learning outcomes.